Bragg-Edge Elastic Strain Tomography for in situ Systems from Energy-Resolved Neutron Transmission Imaging - Hendriks, J N; Gregg, A W T; Wensrich, C M; Tremsin, A S; Shinohara, T; Meylan, M; Kisi, E H; Luzin, V; Kirsten, O (arXiv.org, 2019)
Technological developments in high resolution time-of-flight neutron detectors have raised the prospect of tomographic reconstruction of elastic strain fields from Bragg-edge strain images. This approach holds the potential to provide a unique window into the full triaxial stress field within solid samples. While general tomographic reconstruction from these images has been shown to be ill-posed, an injective link between measurements and boundary deformations exists for systems subject to in situ applied loads in the absence of residual stress. Recent work has provided an algorithm to achieve tomographic reconstruction for this class of mechanical system. This letter details an experimental proof-of-concept for this algorithm involving the full reconstruction of a biaxial strain field within a non-trivial steel sample. This work was carried out on the RADEN energy resolved neutron imaging instrument within the Japan Proton Accelerator Research Complex, with validation through Digital Image Correlation and constant wavelength neutron strain scans.